ANALISIS KEWAJIBAN PAJAK PENGHASILAN PASAL 21, 22, 23, DAN 25 PADA PT XYZ TAHUN 2020 - Stefhany, Audrey; Widjaja, Purnamawati Helen (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study was to determine the compliance of corporate taxpayers of PT XYZ in calculating, payment and reporting tax obligations in 2020. PT XYZ in this case is a corporate taxpayer engaged in automotive interior manufacturing. Data processing techniques used in this study are data reduction, data presentation in tabular form and draw conclusions. The results of this study indicate the compliance of PT XYZ in calculating income tax (PPh Article 21, PPh Article 22, PPh Article 23, and PPh Article 25) in accordance with the laws and regulations regarding income tax as well as payment and reporting taxes before the specified time limit. . The implication of this research is that companies can calculate their income tax and make deposits and reports in accordance with applicable regulations. However, several times the company was late in making payment and reporting.